2019
DOI: 10.1021/acs.orglett.8b03436
|View full text |Cite
|
Sign up to set email alerts
|

Formal Asymmetric Cycloaddition of Activated α,β-Unsaturated Ketones with α-Diazomethylphosphonate Mediated by a Chiral Silver SPINOL Phosphate Catalyst

Abstract: An efficient method for preparing highly functionalized chiral nonspiro-phosphonyl­pyrazolines via an asymmetric formal 1,3-dipolar cycloaddition reaction of α-diazomethyl­phosphonate with activated, acyclic α,β-unsaturated ketones, bearing an additional nitrile electron-withdrawing group, has been developed, utilizing an in situ generated chiral silver phosphate catalyst, affording excellent stereoselectivities (up to 98% ee, 99:1 dr) and yields (up to 95%). A stepwise mechanism is proposed based upon density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Peng developed a general method to synthesize an asymmetric form of 1,3‐dipole using α‐diazomethylphosphonate and activated, acyclic α,β‐unsaturated ketone (with an additional nitrile electron‐absorbing group) (Scheme 79). [ 83 ] The asymmetric cycloaddition reaction catalyzed by chiral silver phosphate from ( R )‐ SPA 32 could prepare highly functionalized chiral non‐spirophosphonopyrazolines with excellent stereoselectivity (up to 98% ee, 99 : 1 d.r.) and high yield (up to 95%).…”
Section: Asymmetric Metal‐organic Cooperative Catalysismentioning
confidence: 99%
“…Peng developed a general method to synthesize an asymmetric form of 1,3‐dipole using α‐diazomethylphosphonate and activated, acyclic α,β‐unsaturated ketone (with an additional nitrile electron‐absorbing group) (Scheme 79). [ 83 ] The asymmetric cycloaddition reaction catalyzed by chiral silver phosphate from ( R )‐ SPA 32 could prepare highly functionalized chiral non‐spirophosphonopyrazolines with excellent stereoselectivity (up to 98% ee, 99 : 1 d.r.) and high yield (up to 95%).…”
Section: Asymmetric Metal‐organic Cooperative Catalysismentioning
confidence: 99%
“…The Smietena group have demonstrated that the reaction of in situ generated SGR anions with α,β‐unsaturated nitriles involves elimination of the cyano group during the aromatization of phosphonylpyrazoles via pyrazoline intermediates under strong basic conditions . The group of Lan and Peng surmised that the aromatization could be inhibited by running the reaction in a weak base medium and successfully realized a chiral silver SPINOL phosphate‐catalyzed asymmetric formal 1,3‐dipolar cycloaddition of α‐diazomethylphosphonate 432b with activated acyclic α,β‐unsaturated ketones bearing additional nitrile groups . The chiral silver phosphate catalyst in situ generated from chiral phosphoric acid 444 and Ag 2 CO 3 allowed the preparation of highly functionalized chiral non‐spiro‐phosphonylpyrazolines 445 from aryl‐ and alkyl‐substituted α,β‐unsaturated ketones 443 in good yields with excellent ee values (Scheme ).…”
Section: Reactions Involving Heterocyclic Ring Formationmentioning
confidence: 99%
“…One typical example is the coupling of diazocarbonyl compounds with α,β-unsaturated carbonyls. Owing to its inherent ylide nature, α-diazocarbonyl compounds are amenable to both 1,2-addition to a carbonyl, leading to homologation, and conjugate addition to an alkene moiety, leading to competitive 1,3-dipolar cycloaddition, C–H insertion, or cyclopropanation (Scheme , I). For example, a chiral titanium catalyst was developed by Maruoka et al to facilitate 1,3-dipolar cycloaddition to yield chiral pyrazole derivatives .…”
Section: Introductionmentioning
confidence: 99%